Lavering Process Mistakes: An Analysis of Contractual Liability Burdening Marketplace Consumers - Aswari, Aan; Asrul Azis, Muhammad Nur; Prawira Buana, Andika (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 3 (2023)DO - 10.24843/JMHU.2023.v12.i03.p01, 2023)
This research aims to describe the urgency of consumer rights in a consumer protection, especially related to services in the process or period of carrying out the obligation to deliver goods that are not complete when consumer obligations have been carried out, there is a period of control of the object on the delivery service that risks defects in part or all of the things promised. Observation and interviews are used as research methods for this article to find legal actions. The results of this study reveal the urgency of consumer rights must continue to be maintained and developed because there is a period of control of the object transacted in the lavering process resulting in one of the obligations of the entire series of obligations on the agreed object not being carried out, normatively still providing legal protection to consumers. The factor of inadequate facilities to accommodate comments addressed to the party that should be responsible for errors, the factor of lack of public knowledge in determining the legal subject that should be responsible. The recommendation of this article is that the provider of the transacted object gives a report to the organizing agent to pay attention to consumer input in the feedback column so that justice for the seller and buyer can be realized, not the other way around, namely the seller getting a bad reputation from the buyer, and the buyer losing the wealth he has spent due to an untrustworthy courier service.